The Skandapurāṇa / Vol. 3 Adhyāyas 34,1 - 61, 53 - 69 : the Vindhyavāsinī cycle / critical ed. with an introd. & annotated Engl. synopsis by Yuko Yokochi - Yokochi, Yūko (The Skandapurāṇa, 2013)
Preliminary material -- Introduction -- Synopsis -- Skandapurāṇa 34.1–61, 53–69 -- Bibliography -- Indexes.